Between the Plantation and the Port: Racialization and Social Control in Eighteenth-Century Paramaribo. (26th March 2019) - Brandon, Pepijn
Abstract: Starting from an incident in the colonial port city of Paramaribo in the autumn of 1750 in which, according to the Dutch governor Mauricius, many of the proper barriers separating rich and poor, men and women, adults and children, white citizens and black slaves were crossed, this article traces some of the complexities of everyday social control in colonial Suriname. As gateways for the trade in commodities and the movement of people, meeting points for free and unfree labourers, and administrative centres for emerging colonial settlements, early modern port cities became focal points for policing interaction across racial and social boundaries. Much of the literature on the relationship between slavery and race focuses on the plantation as "race-making institution" and the planter class as the immediate progenitors of "racial capitalism". Studies of urban slavery, on the other hand, have emphasized the greater possibilities of social contact between blacks, mestizos, and whites of various social status in the bustling port cities of the Atlantic. This article attempts to understand practices of racialization and control in the port city of Paramaribo not by contrasting the city with its plantation environment, but by underlining the connections between the two social settings that together shaped colonial geography. The article focuses on everyday activities in Paramaribo (dancing, working, drinking, arguing) that reveal the extent of contact between slaves and non-slaves. The imposition of racialized forms of repression that set one group against the other, frequently understood primarily as a means to justify the apparent stasis of the plantation system with its rigid internal divisions, in practice often functioned precisely to fight the pernicious effects of mobility in mixed social contexts.